Pembinaan Pencak Silat di Perguruan Pencak Silat Se-Kabupaten Wonogiri - Eddy Hartoyo, Abdul Rosyid (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to know about martial arts training consists of, athletes, coaches, organization,facilities and infrastructure, support,atCollegePencakSilatSe-Wonogiriyear2013/2014. The approach used inthis research is descriptive qualitative approach. Locations and targets in 3 Pencak silat college in the Wonogiriinton distric.The results of the study are: 1) the quality of athletes in accordance with the theory and Pencaksilat expert in process capability measurement method is not a good athlete and a good recruitment processalmost all ASAD persinas just not good 2) in accordance with the theory of quality trainers and experts martialarts is not good because not all coaches are certified, and do not develop exercise programs, exercise programs in accordance with the theory and martial arts expert is not good berkriteria 3) the quality of the organization in accordance with the theory and pencak silat expert is not good because it has a full member, but does not provide a program division of labor and the management. 4) in accordance with the theory and expert pencak silat infrastructure is good enough 5) factors support in accordance with the theory and pencak silat expert who just Persinas ASAD berkriteria unfavorable because the support of the community in the form of sponsorship, and 2 other universities is not good because it does not have the support factor. It was concluded that the process of pencak silat training in accordance with the theory Wonogiri and martial arts expert berkriteria unfavorable